2018
DOI: 10.1186/s12884-018-1730-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of women’s utilization of primary health care for skilled pregnancy care in rural Nigeria

Abstract: BackgroundAlthough Primary Health Care (PHC) was designed to provide universal access to skilled pregnancy care for the prevention of maternal deaths, very little is known of the factors that predict the use of PHC for skilled maternity care in rural parts of Nigeria - where its use is likely to have a greater positive impact on maternal health care. The objective of this study was to identify the factors that lead pregnant women to use or not use existing primary health care facilities for antenatal and deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(108 citation statements)
references
References 32 publications
7
97
3
1
Order By: Relevance
“…However, there were differences in the proportion of married women, those with at least a tertiary education, and primigravid in Southeastern Nigeria and AKUH, N [ 8 ]. Being married has been associated with increased utilization of maternal health services in different studies as previously discussed [ 15 , 17 , 20 ]. All women in the Southeastern Nigeria study were married but despite that, there was a lower level of PCC in comparison to AKUH, N women.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were differences in the proportion of married women, those with at least a tertiary education, and primigravid in Southeastern Nigeria and AKUH, N [ 8 ]. Being married has been associated with increased utilization of maternal health services in different studies as previously discussed [ 15 , 17 , 20 ]. All women in the Southeastern Nigeria study were married but despite that, there was a lower level of PCC in comparison to AKUH, N women.…”
Section: Discussionmentioning
confidence: 99%
“…Alternately, studies have found empowerment to be positively associated with increased pregnancy healthcare seeking [37,38], skilled delivery attendance [37,39] and the use of modern contraceptive methods [5,40], resulting in lower infant mortality [41]. While there are many ways to conceptualize women's empowerment, previous studies have conceptualized empowerment as it relates to pregnancy outcomes, such as via health decision-making [42], attitudes toward intimate partner violence [13], education [13,43], employment [44,45] wealth [22], access to media [22] and contraceptive use [31].…”
Section: Anc and Women's Empowermentmentioning
confidence: 99%
“…Home deliveries in Nigeria are usually characterized by unhygienic environment, use of unsterilized sharps and poor cord care 20,21. It is sad to note that despite attendance for antenatal care in health facilities, many women for a number of reasons still choose to deliver at home. The prevalence of home deliveries among women who attend antenatal clinic is in the range of 15-74%, with the higher prevalence in northern Nigeria [22][23][24] . There are several factors that contribute to this unfortunate incidence and they include inaccessibility to health facilities, labour occurring at night, attitude of health workers to pregnant women and high cost of delivery in some health facilities.…”
Section: Discussionmentioning
confidence: 99%